2007
DOI: 10.1108/02621710710819348
|View full text |Cite
|
Sign up to set email alerts
|

A study of managerial derailment characteristics and personality preferences

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…Despite the costly outcomes of managerial derailment, very little research has investigated factors that relate to derailment, the potential to derail, or even perceptions of derailment. Previous derailment research has shown that lack of managerial skills or certain aspects of a manager's personality may relate to derailment or perceptions of potential derailment (Gentry, Mondore, & Cox, 2007; Hogan & Hogan, 2001; Shipper & Dillard, 2000). The present research extends what is known about antecedents of the perceptions of characteristics and behaviors that may lead to potential derailment.…”
mentioning
confidence: 99%
“…Despite the costly outcomes of managerial derailment, very little research has investigated factors that relate to derailment, the potential to derail, or even perceptions of derailment. Previous derailment research has shown that lack of managerial skills or certain aspects of a manager's personality may relate to derailment or perceptions of potential derailment (Gentry, Mondore, & Cox, 2007; Hogan & Hogan, 2001; Shipper & Dillard, 2000). The present research extends what is known about antecedents of the perceptions of characteristics and behaviors that may lead to potential derailment.…”
mentioning
confidence: 99%
“…Swinburne, 1985) and grounded (alert to practical needs; concerned with immediate interest/issues; dependable; practical judgement, cf. Gentry et al, 2007) at the 5% level, than their student counterparts. Given Ryckman's (1997) assumptions that: (i) personality profiles are dynamic; (ii) there exists an innate growth that moves individuals toward realisation of their potential, given appropriate environmental conditions; and (ii) most of our personality or behaviour is learned, purposive and that we are motivated to attain certain goals, it is incumbent on educators and trainers to assess as objectively as possible the inputs to the overall programme and the subsequent outputs.…”
Section: Resultsmentioning
confidence: 63%
“…Research has confirmed that personality is a key contributor to effective management especially in the service sector where welldeveloped personal and interpersonal competencies are a key to managerial success (for example Barrick and Mount, 1991;Gallon, 1994;Gentry et al, 2007;Havaleschka, 1999;Judge et al, 1995;Stone, 1988;Verbeke, 1994;Worsfold, 1989). The current study is based on the premise that that personality profiles are dynamic, may be adapted by individuals in order to realise their potential and that, given appropriate environmental conditions, most of our personality or behaviour is learned and purposive, and that we are motivated to attain certain goals (Ryckman, 1997).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Block, 1995;Gentry et al, 2007). However, more recent support and evidence show that the BFI has emerged as the paradigm for studying personality traits and their wider influence (John and Naumann, 2010).…”
Section: The Big Five Inventorymentioning
confidence: 99%